COURSES FOR STUDENTS SPECIALIZING IN INDUSTRIAL ACCOUNTING. - Gordon, Dennis (The Accounting Review, 1950)
Abstract Many questions arise related to courses to be taken by accounting students if they plan to enter industrial accounting. At the University of Akron, Ohio, the Akron chapter of the National Association of Cost Accountants (NACA) formed an educational guidance committee to help students. The University of Akron sought the assistance of the Akron chapter for the purpose of improving its curriculum and aiding the students who would be working for employers represented by the wide membership of NACA. The University turned to the Akron chapter because it includes accountants engaged in a wide range of activities, from the one-man accounting office to the controllers of some of America's largest factories. All types of educational backgrounds, from those who studied their accounting by correspondence to graduates of colleges in every region of the country are represented in its membership. Conditions change, jobs change, so the educator believes that a broad, firm foundation enables a student to progress vocationally much farther in the long run, and in addition, make him a whole, well-rounded person rather than a narrow technician.